SUPERVISI KUNJUNGAN KELAS UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK GURU SDN CUKIL 01, TENGARAN, KABUPATEN SEMARANG - Argiani, Astiti Rahayu; Slameto, Slameto (Universitas Kristen Satya Wacana, 2015)
The problems background in the learning process, teacher and pupils are interpedently connected to one another in the learning classroom process, it is becauseÂ conversation and encounter process occurred. This learning process is not an uncommonÂ issue. The problems are teacher has not finish classroom materials for the learningÂ process, which cause an impact on the learning processâs implementation, teacher hasÂ not developed educational learningâs process, and teacher has not mastered todayâsÂ technology. Based on those complications, the best solution is implementing classroomâsÂ visits supervision. The problemâs formulation in this study is whether the supervision ofÂ classroom visit can improve teacherâs pedagogical competence at Elementary SchoolÂ of Cukil 01, Tengaran. The researchâs purpose is to enhance teacherâs pedagogical competence though the classroom visitâs supervision at Elementary School of Cukil 01,Â Tengaran The researchâs type is school action research which is applied through theÂ phase of identification of focusâs areas, data gathering, analyzes and data interpretation,Â planâs arranging, and implementation of the action. The researchâs subject is ten teachersÂ through interview and also documentary study. The data gatheringâs technique usedÂ though interview, observation, questionnaire, and also documentary study. The dataÂ processingâs techniques are done with data classifying, data presentation andÂ verification. The validity of test data is using dataâs triangulation. The researchâs resultÂ shows two point they are: (1) The implementation of classroom visitâs supervision obtains a maximum score, that is 94% with a very good criteria (AB) and minimum score is 74%Â with a good criteria (B). Feedback that is performed also given which is showed areÂ mostly positive answers. (2) The teacherâs pedagogical competence obtains a maximumÂ score, that is 88% with very good criteria (AB) and a minimum score is 70% with aÂ good criteria (B).To conclude the researchâs result, through the classroom visitâsÂ supervision is able to improve the teacherâs competence at Elementary School of CukilÂ 01, Tengaran. Suggestions offered, there should be continuity of the classroom visitâsÂ supervision in the school that agree by all teachers to improve the teachersâ competenceÂ in the implementation of learning.